Pengaruh Penggunaan Media Audio Visual Terhadap Kemandirian Menggosok Gigi Pada Anak Tunagrahita Kategori Ringan Di Sekolah Luar Biasa Mandara Kendari - Wa Ode Aisa Zoahira; Tasrun, La Ode (Politeknik Baubau, 2025)
Data the number of mentally retarded children in 2019 at the Mandara Kendari Spescial School totaled 35 people. Based on interviews with teachers at Mandara Kendari Spescial School , a problem was encountered, namely students with mental retardation in the mild category still found difficult to brush the teeth parts of the teeth that were located inside such as the right and left teeth and the inside, students were only able to scrub certain parts such as parts the front and part of the graham or chewing teeth. This was caused there was no routine activity of brushing teeth at school. Objective : This study aims to determine the effect of the use of audiovisual media on the independence of brushing teeth in mild mental retardation children at Special School of Mandara Kendari Spescial School . Methods: Type of research was a quasy experimental study with a control group pre-test-design. The study population was all mentally retarded students registered as students at Mandara Kendari Spescial School in 2020 were 35 people with a sample size were16 people. The sampling technique used accidental sampling, the method of analysis used Paired T test. Results : showed that there was an effect of the use of audiovisual media on the independence of brushing teeth in mild mental retardation children at Mandara Kendari Spescial School (P value = 0.000 <0.05).Conclusion: was that there was an effect of the use of audiovisual media on the independence of brushing teeth in mild mental retardation children. Keywords: Independence brushing teeth, audiovisual media, mentally retarded children, Biopharmacy.